Modelisation numerique des transferts d'humidite en milieux poreux - Tallec, Patrick Le; Nicolas, Pierre (European Journal of Computational Mechanics, 1994)
We are dealing with the numerical modelling of a macroscopic model describing humidity transfers through porous media. The model takes into account the liquid-vapour phase change, the variation of the total gas pressure and some hysteretic effects. The unknowns are the temperature and the apparent densities of air, of water vapour and of liquid water. Finite volumes and finite elements are used together, which ensures that the approximation is stable and conservative. The discretization scheme in time .is a totally implicit scheme combined with a Newton algorithm for the solution of the nonlinear system. Different numerical simulations involving mortar as porous media are presented.